The Physical Education teacher and ethnocentrism: a study on bullying (Research, Society and Development, 2020)
The present study analyzes the perceptions and behaviors of three physical education teachers at the Federal Institute of Piauí - Campus Teresina Central, regarding manifestations of bullying and ethnocentric postures in the school environment. It is a qualitative research, through discourse analysis. The study is an excerpt of the doctoral research that has as its object bullying in the handball classes of the institution. The phenomenon was verified in the handball classes, the interest in investigating the existence of this syndrome in other modalities arose. The results proved the existence of this phenomenon and these postures in the school universe, generating situations of conflict, revolt and apathy. Teachers alleged weaknesses in their training to deal with this problem in an appropriate way. Consequently, they attested that their attitudes towards situations have been ineffective and inefficient. In this way, it is noticed a certain disregard of the institution in relation to the training of teachers to deal with situations like these.